If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + 17x + -3 = 9x + 31 + -7x Reorder the terms: 4 + -3 + 17x = 9x + 31 + -7x Combine like terms: 4 + -3 = 1 1 + 17x = 9x + 31 + -7x Reorder the terms: 1 + 17x = 31 + 9x + -7x Combine like terms: 9x + -7x = 2x 1 + 17x = 31 + 2x Solving 1 + 17x = 31 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 17x + -2x = 31 + 2x + -2x Combine like terms: 17x + -2x = 15x 1 + 15x = 31 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 15x = 31 + 0 1 + 15x = 31 Add '-1' to each side of the equation. 1 + -1 + 15x = 31 + -1 Combine like terms: 1 + -1 = 0 0 + 15x = 31 + -1 15x = 31 + -1 Combine like terms: 31 + -1 = 30 15x = 30 Divide each side by '15'. x = 2 Simplifying x = 2
| 3x-4=56-9x | | 9x+13=-8 | | 10x+3=4x+39 | | 3,570=34(p+30) | | 90=30x | | 6n^3-4n^2= | | 6m^2-23m-18=0 | | 5x^2+2c+8=0 | | 6x-yx=5 | | ln(5-3)=ln(5)-ln(3) | | c(x)=7x+569 | | 52=c-46 | | x(x+8)-(25x+3x)=0 | | (-7+9i)+(2-10i)= | | -3x-2y+z=11 | | 6x-77+7x+11=4x-60+3x | | 12x-45=26-3x-4 | | 5x^2+2c+7=0 | | r-46=15 | | 6x-77-7x+11=4x-60-3x | | 30=3v | | x=3-1y | | 7=56j | | 750-50x=-185 | | 2ln(7x)=5 | | y-4.1=5.4 | | a^2+12a-21=0 | | X+(11)=13 | | 3b-5=-44 | | 42x^2-18x= | | ln(5+3)=ln(5)+ln(3) | | E-14=0 |